Reconceptualizing Idol Making in the Context of Bangladesh - Haque, Mohammad Ainul (Advances in Social Sciences Research Journal, 2022)
While bringing into attention the creative skills of a local Idol maker, this paper aims at exploring Idol making in the light of the maker’s perception and simultaneously placing it within the broader social and cultural context of Bangladesh. It seeks to understand the meaning that idol-making carries to its creator, and the meaning of idol-making that is felt within the larger social context of Bangladesh. While doing so, this paper investigates the concept of art prevailing in contemporary Bangladeshi society and therefore, examines the creative dimensions of idol making from folkloristic and material culture perspectives. Along with bringing forth the unheard stories of a local Bangladeshi idol maker, this paper aims at dismantling the grand narratives of art that existed within Bengali society and therefore, provides an opportunity to reconceptualize the artistic dimension of local idol making in Bangladesh.